Brad’s Sure Guide to SQL Server Maintenance Plans - McGehee, Brad M. (Simple Talk Publishing, 2011)
In his new book, Brad's Sure Guide to SQL Server Maintenance Plans, Brad McGehee takes you on a comprehensive tour of two SQL Server tools designed to help DBAs ensure that a "required minimum" level of maintenance takes place on their SQL Server instances: the Maintenance Plan Wizard and the Maintenance Plan Designer.